Hyperfine Effects in Ligand NMR: Paramagnetic Ru(III) Complexes with 3-Substituted Pyridines - Novotný, Jan; Přichystal, David; Sojka, Martin; Komorovsky, Stanislav; Nečas, Marek; Marek, Radek (Inorganic chemistry, 2018)
NMR spectroscopy is an indispensable tool in characterizing molecular systems, including transition-metal complexes. However, paramagnetic transition-metal complexes such as those with ruthenium in the +3 oxidation state are troublemakers because their unpaired electrons induce a fast nuclear spin relaxation that significantly broadens their NMR resonances. We recently demonstrated that the electronic and spin structures of paramagnetic Ru(III) systems can be characterized in unprecedented details by combining experimental NMR results with relativistic density-functional theory ( Novotny et al. J. Am. Chem. Soc. 2016 , 138 , 8432 ). In this study we focus on paramagnetic analogs of NAMI with the general structure [3-R-pyH]+trans-[RuIIICl4(DMSO)(3-R-py)]-, where 3-R-py stands for a 3-substituted pyridine. The experimental NMR data are interpreted in terms of the contributions of hyperfine (HF) NMR shielding and the distribution of spin density calculated using relativistic DFT. The DFT computational methodology is evaluated, and the effects of substituents, environment, and relativity on the hyperfine shielding are discussed. Particular attention is paid to the analysis of the fundamental Fermi-contact (FC), spin-dipole (SD), and paramagnetic spin-orbit (PSO) terms that contribute to the hyperfine 1H and 13C NMR shifts of the individual atoms in the pyridine ligands and the spin-polarization effects in the ligand system that are linked to the character of the metal-ligand bond. The individual HF shielding terms are systematically discussed as they relate to the traditional, but somewhat mixed, contact and pseudocontact NMR contributions used extensively by experimental spectroscopists in biomolecular NMR and the development of PARACEST magnetic-resonance contrast agents.